Anti-Ulcer and Antioxidant Activities of Chrysophyllum albidum G. Don. Seeds Cotyledons - Owolabi, Tunde; Okubor, Philippine (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2024)
Background: Gastric ulcers are prevalent gastrointestinal disorders with significant global implications owing to their prevalence and potential complications. Side effects associated with synthetic drugs have led to the search for alternative treatments. Chrysophyllum albidum, a plant traditionally used to manage various diseases, has been investigated for its potential to alleviate ulcerative conditions. Methods: This study assessed the efficacy of extracts from C. albidum seed cotyledons in mitigating ethanol- and diclofenac-induced ulcers in rats. Phytochemical screening was performed using standard methods and antioxidant activities were evaluated using DPPH scavenging and ABTS+-reducing assays. Results: For ethanol-induced gastric ulcers, extracts at doses of 100, 200, and 400 mg/kg produced lesion indices of 7.04 ± 0.44, 5.18 ± 0.38, and 2.53 ± 0.46 mm, respectively, compared to omeprazole's 0.9 ± 1.09 mm. The highest dose showed 87.93% inhibition, which was comparable to that of omeprazole (93.63% inhibition). A similar trend was observed for diclofenac-induced ulcers. Phytochemical analysis revealed the presence of active compounds, such as steroids, flavonoids, polysaccharides, alkaloids, and cardiac glycosides. Antioxidant activity results indicated significant free radical scavenging properties, with an IC50 value of 49.24 µg/mL for DPPH and 15.1 µg/mL for ABTS+ at a dose of 400 mg/kg. These findings demonstrate the notable dose-dependent anti-gastritis and anti-ulcer effects of the extract. Conclusion: This study highlights the potential of C. albidum seed cotyledons as a valuable candidate for gastroprotective drug development and supports their traditional use in treating and preventing gastritis and gastric ulcers.